Differential contributions of prefrontal and hippocampal dopamine D(1) and D(2) receptors in human cognitive functions - Takahashi, Hidehiko; Kato, Motoichiro; Takano, Harumasa; Arakawa, Ryosuke; Okumura, Masaki; Otsuka, Tatsui; Kodaka, Fumitoshi; Hayashi, Mika; Okubo, Yoshiro; Ito, Hiroshi; Suhara, Tetsuya (The Journal of neuroscience, 2008)
Dopamine D(1) receptors in the prefrontal cortex (PFC) are important for prefrontal functions, and it is suggested that stimulation of prefrontal D(1) receptors induces an inverted U-shaped response, such that too little or too much D(1) receptor stimulation impairs prefrontal functions. Less is known of the role of D(2) receptors in cognition, but previous studies showed that D(2) receptors in the hippocampus (HPC) might play some roles via HPC-PFC interactions. We measured both D(1) and D(2) receptors in PFC and HPC using positron emission tomography in healthy subjects, with the aim of elucidating how regional D(1) and D(2) receptors are differentially involved in frontal lobe functions and memory. We found an inverted U-shaped relation between prefrontal D(1) receptor binding and Wisconsin Card Sorting Test performance. However, prefrontal D(2) binding has no relation with any neuropsychological measures. Hippocampal D(2) receptor binding showed positive linear correlations not only with memory function but also with frontal lobe functions, but hippocampal D(1) receptor binding had no association with any memory and prefrontal functions. Hippocampal D(2) receptors seem to contribute to local hippocampal functions (long-term memory) and to modulation of brain functions outside HPC ("frontal lobe functions"), which are mainly subserved by PFC, via the HPC-PFC pathway. Our findings suggest that orchestration of prefrontal D(1) receptors and hippocampal D(2) receptors might be necessary for human executive function including working memory.